Spirituality among flood victims: A comparison between two states - Sipon, Sapora; Sakdan, Mohd Fo'ad; Mustaffa, Che Su; Ahmad Marzuki, Najib; Khalid, Mohamad Sukeri; Ariffin, Mohd Taib; Nik Nazli, Nik Nadian Nisa; Abdullah, Salhah (Elsevier Ltd., 2015)
In the field of psychological research, more and more studies suggest ways that spirituality and religiosity is important in dealing with life’s problems including flood disaster. Many mental health workers considered seeking a spiritual understanding of one’s place in the universe is important in overall health and well-being including disaster management intervention. Given the potential effects of spiritual and religious beliefs on coping with traumatic events such as flood disaster, the study of the role of spirituality in fostering resilience in flood disaster survivors may facilitate the understanding of human adaptation to trauma. This paper is based on quantitative and qualitative approach conducted on three groups of flood victims from two different states in Malaysia. The findings show that there was no significant difference on spirituality among the two states studied.